The Prognosis of In Vitro Fertilization (IVF) : a Regression Approach - Baeten, S.; Bouckaert, A.; Thomas, K.; Loumaye, E. (Methods of Information in Medicine, 1988)
Logistic regression can be used to investigate prognostic factors in the treatment of infertility by in vitro fertilization (IVF). It was observed that the probability of success is not constant over repeated attempts, but decreases according to a selection process. Another prognostic factor, the number of cells of the largest embryo, was also observed.
Keywords: Regression; Infertility; Gynecology; Modelling; IVF